PENERAPAN COST-VOLUME-PROFIT ANALYSIS UNTUK PERENCANAAN LABA PADA CV VEREL TRI PUTRA MANDIRI MANADO - Pangemanan, Melisa Veronica; Morasa, Jenny; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2021)
The company is one of the supporting aspects of a country's economy. Good planning in the company can help companies to achieve company goals. CV Verel Tri Putra Mandiri is a company engaged in the culinary field, namely producing bread as a product of this company. CV Verel Tri Putra Mandiri until now has not used any analytical tools to be used as a reference in profit planning. The research objective is to implement profit planning using the Cost-Volume-Profit (CVP) method. This type of research uses descriptive qualitative research obtained by direct observation and interviews. The data analysis method carried out in this study passed through 4 (four) stages, namely knowing, break event point, contribution margin, margin of safety and operating leverage. The research results of CV Verel Tri Putra Mandiri experienced a decrease in income and profit in 2020 compared to 2019. Where income decreased by 55.69% or Rp. 63.595.000,-. And a profit of 25.76% or Rp. 36.673.1010,-. which causes a decrease in the contribution margin, margin of safety and an increase in the company's break-even point. This is due to the Covid-19 pandemic and the implementation of the Community Activity Border (PPKM).